What is the expression -7(3z + 5t – 3g) in simplest form?​

What is the expression -7(3z + 5t - 3g) in simplest form?​

Related Posts

This Post Has 3 Comments

  1. -3z-5t+3g

    Step-by-step explanation:

    -7(3z+5t-3g)

    = -7×3z +( -7×5t)( -7×-3g)

    = -21z-35t+21g

    divide all elements by 7

    = -21÷7 -35÷7+21÷7

    = -3z-5t+3g

  2. correct answer is infinitely many solutions

    step-by-step explanation:

    2(2x + 3) = -4 + 2(2x + 5)

    solving the above equation:

    4x + 6 = -4 +4x +10

    combining like terms

    4x -4x = -4+10-6

    0=0

    since both sides are 0=0, we end up into true statement it means it has infinite many solutions.

    so correct answer is infinitely many solutions

  3. first, we define the variables:

    x: number of years after 1950

    f (x): amount of vinyl sold.

    then, with the variables defined, we have:

    68594 vinyl records were sold in 1958 > f (8) = 68594

    91299 vinyl records were sold in 1961 > f (11) = 91299

    38720 vinyl records were sold in 1952 > f (2) = 38720

    161743 vinyl records were sold in 1967 > f (17) = 161743

    read more on -

    step-by-step explanation:

Leave a Reply

Your email address will not be published. Required fields are marked *